Réponses

2013-04-04T22:23:44+02:00

Je te l'ai déjà fait... :s

 

1)a) 

f(1) = 1,3 * 1 = 1,3 \\f(4) = 1,3*4=5,2 \\f(1)+f(4) = 1,3 + 5,2 = 6,5 \\ \\f(1+4)=f(5)=1,3*5=6,5 \\ \\f(1)+f(4) = f(1+4)

 

b) f(-5) = 1,3 * -5 = -6,5 \\f(3) = 1,3*3=3,9 \\f(-5)+f(3) = -6,5 + 3,9 = -2,6 \\ \\f(-5+3)=f(-2)=1,3*-2=-2,6 \\ \\f(-5)+f(3) = f(-5+3)

 

2) f(x) = 1,3x \\f(x')=1,3x' \\f(x)+f(x') = 1,3x + 1,3x' \\f(x)+f(x') = 1,3(x+x') \\f(x)+f(x') = f(x+x') 

 

3) f(12) = 1.3 * 12 = 15.6 \\f(13) = 1.3 * 13 = 16.9 \\ \\f(12 + 13) = f(25) \\f(12+13) = f(12) + f(13) \\f(25) = f(12) + f(13) = 15,6 + 16,9 = 32,5 \\ \\25 equerres => 32,5euros